Development and assessment of ceria–propylene glycol nanofluid as an alternative to propylene glycol for cooling applications. (5th June 2016) - Prabhakaran, M.; Manikandan, S.; Suganthi, K.S.; Leela Vinodhan, V.; Rajan, K.S.
Highlights: Stable ceria–propylene glycol nanofluids prepared by probe ultrasonication. These nanofluids possess higher thermal conductivity & volumetric specific heat. Particle clustering & Brownian motion contribute to thermal conductivity increase. 1 vol.% ceria–PG viscosity lower than PG viscosity at temperatures <80 °C. Heat absorption by nanofluids increase with nanoparticle concentration. Abstract: Spherical, crystalline ceria nanoparticles of 18–25 nm were synthesized from cerium nitrate precursor. The dispersion of as-synthesized ceria nanoparticles in propylene glycol was achieved through extended probe ultrasonication for 14 h, leading to ceria–propylene glycol nanofluids. The influence of nanoparticle concentration (0–1 vol.%) and temperature on viscosity and thermal conductivity of ceria–propylene glycol nanofluids were investigated. Our data indicate that the higher thermal conductivity enhancement at elevated temperatures (18.8% at 80 °C for 1 vol.% nanofluid) can be attributed to the particle clustering and Brownian-motion induced microconvection. Ceria nanoparticles interact with propylene glycol leading to disturbance in hydrogen bonding network prevalent in propylene glycol. This resulted in lower viscosity of 0.5 vol.% and 1 vol.% ceria–propylene glycol nanofluids than propylene glycol over a wide range of temperatures. The heat absorption by ceria–propylene glycol nanofluids under transient, natural convective heat transfer conditions increased with ceria nanoparticle concentration. Hence ceria–propylene glycol nanofluids are suitable for cooling applications.